Relationship Between Parenting Style and Food Consumption Patterns and the Incidence of Stunting in Toddlers Aged 24–60 Months in the X Community Health Center Area - Meku, Fransiskus Xaverius; Hambur, Sesilia Gratia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Stunting is defined as a condition where children under five have a height-for-age z-score below -2 SD (stunted) or below -3 SD (severely stunted). In Lelak District, efforts to reduce stunting have begun at the village level, but key factors like parenting style and dietary habits still need improvement. This study aimed to examine the relationship between parenting style, food consumption patterns, and stunting among toddlers aged 24–60 months in the X Community Health Center area. A retrospective cross-sectional design was used, involving 60 mothers of stunted children selected through purposive sampling from Bangka Lelak and Lentang Villages. Parenting style was assessed using a validated questionnaire, while dietary patterns were measured through a Food Frequency Questionnaire (FFQ). Stunting data were obtained from height measurements recorded by the community health center. Results showed that 36.7% of respondents practiced permissive parenting, and 86.7% had poor dietary patterns. Overall, 70% of the toddlers were stunted. The Spearman Rank test revealed a significant relationship between parenting style and stunting (p = 0.000), as well as between dietary patterns and stunting (p = 0.000). Logistic regression analysis indicated that children of mothers with poor parenting were 0.159 times more likely to be stunted, and those with poor dietary practices were 0.043 times more likely to experience stunting. In conclusion, poor parenting and inadequate food consumption significantly contribute to stunting. Interventions focusing on improving parenting skills and nutritional awareness are essential for effective stunting prevention.